Dinamika Opini Publik terhadap Undang-Undang Pelindungan Data Pribadi (Kasus Percakapan Media Sosial X) - Dahana, Abyzan Syahadin Bagja (Jurnal Media dan Komunikasi Indonesia, 2024)
This study aims to describe the dynamics of public opinion in X around the Data Protection Law (UU PDP) that emerged before and after its ratification. Previous research on the UU PDP has only focused on normative juridical aspects but not on public opinion aspects. In fact, research on public opinion is important because public opinion has the power to advocate. This study analyzed 3,374 tweets about the UU PDP published from January 24, 2020, to October 17, 2023. Researchers obtained the data using the scraping method using the Python twscrape library based on the search keywords “Undang-Undang Pelindungan Data Pribadi", “UU PDP", and "RUU PDP". This study adopts the sentiment analysis model of the Indonesian RoBERTa Base Sentiment Classifier and found that neutral-tone tweets dominated conversations that arose before and after the president's passing of the PDP law. A qualitative analysis of the word cloud shows that neutral-tone tweets are facts related to the UU PDP. Negative opinion dominated public opinion against the UU PDP in both conversation periods. The dynamics of public opinion towards the UU PDP reflect the digital movement of opinion (DMO). This is because the number of opinion tweets is volatile and always depends on the intensity of the facts and important momentum related to the UU PDP.Key words: sentiment analysis, public opinion, Data Protection Law, UU PDP, X